1998
DOI: 10.1242/jcs.111.5.645
|View full text |Cite
|
Sign up to set email alerts
|

A novel signal transduction cascade in capacitating human spermatozoa characterised by a redox-regulated, cAMP-mediated induction of tyrosine phosphorylation

Abstract: Capacitation is a priming event that renders mammalian spermatozoa responsive to signals originating from the cumulus-oocyte complex. The attainment of a capacitated state is dependent upon an increase in tyrosine phosphorylation and results in the acquisition of responsiveness to physiological agonists such as progesterone and ZP3. In this study we have shown that this capacitation-dependent increase in tyrosine phosphorylation is controlled by a unique redox-regulated, cAMP-mediated, signal transduction casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Although some level of inhibitor unspecificity cannot be excluded especially for the highest concentrations, the finding that PF431396 significantly inhibits Ca 2+ levels at a concentration similar to that reported to affect both PYK2 activation and pTyr during human sperm capacitation (Battistone et al, 2014), supports a role for this signaling pathway in intracellular Ca 2+ level regulation. Our observations are consistent with the inhibition in Ca 2+ increase detected in sperm exposed to the PKA inhibitor H89, extensively reported to affect pTyr in human sperm (Aitken, Harkiss, Knox, Paterson, & Irvine, 1998;Battistone et al, 2013). Because PF431396 does not affect PKA activation (Alvau et al, 2016;Battistone et al, 2014), the present results suggest that PKA inhibition affects Ca 2+ levels by regulating pTyr.…”
supporting
confidence: 92%
“…Although some level of inhibitor unspecificity cannot be excluded especially for the highest concentrations, the finding that PF431396 significantly inhibits Ca 2+ levels at a concentration similar to that reported to affect both PYK2 activation and pTyr during human sperm capacitation (Battistone et al, 2014), supports a role for this signaling pathway in intracellular Ca 2+ level regulation. Our observations are consistent with the inhibition in Ca 2+ increase detected in sperm exposed to the PKA inhibitor H89, extensively reported to affect pTyr in human sperm (Aitken, Harkiss, Knox, Paterson, & Irvine, 1998;Battistone et al, 2013). Because PF431396 does not affect PKA activation (Alvau et al, 2016;Battistone et al, 2014), the present results suggest that PKA inhibition affects Ca 2+ levels by regulating pTyr.…”
supporting
confidence: 92%
“…Reports have indicated two main changes occurring at the cellular level responsible for sperm capacitation including the generation of physiological levels of ROS and phosphorylation of protein tyrosine. It was found that ROS induces phosphorylation as in-vitro inhibition of ROS by the A c c e p t e d A r t i c l e introduction of 2-deoxyglucose resulted in a reduced concentration of tyrosine-phosphorylated proteins [20]. The process is triggered by an influx of calcium (Ca 2+ ) and bicarbonate ions.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…A key capacitation marker is the activation of a specific signal transduction pathway leading to protein tyrosine phosphorylation [ 50 , 51 ]. It is driven by cyclic adenosine monophosphate (cAMP) and is modulated by the redox status of the cells [ 52 , 53 , 54 , 55 , 56 ]. Interestingly, an elevation of the cAMP synthesis in rat Leydig cells after in vitro treatment with D-Asp was reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%